A systematic review of artificial intelligence tools for chronic pulmonary embolism on CT pulmonary angiography - Abdulaal, Lojain; Maiter, Ahmed; Salehi, Mahan; Sharkey, Michael; Alnasser, Turki; Garg, Pankaj; Rajaram, Smitha; Hill, Catherine; Johns, Christopher; Rothman, Alex Matthew Knox; Dwivedi, Krit; Kiely, David G.; et al. (Frontiers in Radiology, 2024)
Background: Chronic pulmonary embolism (PE) may result in pulmonary hypertension (CTEPH). Automated CT pulmonary angiography (CTPA) interpretation using artificial intelligence (AI) tools has the potential for improving diagnostic accuracy, reducing delays to diagnosis and yielding novel information of clinical value in CTEPH. This systematic review aimed to identify and appraise existing studies presenting AI tools for CTPA in the context of chronic PE and CTEPH. Methods: MEDLINE and EMBASE databases were searched on 11 September 2023. Journal publications presenting AI tools for CTPA in patients with chronic PE or CTEPH were eligible for inclusion. Information about model design, training and testing was extracted. Study quality was assessed using compliance with the Checklist for Artificial Intelligence in Medical Imaging (CLAIM). Results: Five studies were eligible for inclusion, all of which presented deep learning AI models to evaluate PE. Vainio et al. (2021) evaluated the lung parenchymal changes in chronic PE and two studies used an AI model to classify PE, with none directly assessing the pulmonary arteries. Vainio et al. (2023) developed a CNN tool to distinguish chronic PE using 2D maximum intensity projection reconstructions. Bird et al. (2023) study assessed a novel automated approach to quantify hypoperfusion to help in the severity assessment of CTEPH. While descriptions of model design and training were reliable, descriptions of the datasets used in training and testing were more inconsistent. Conclusion: In contrast to AI tools for evaluation of acute PE, there has been limited investigation of AI-based approaches to characterising chronic PE and CTEPH on CTPA.Existing studies are limited by inconsistent reporting of the data used to train and test their models. This systematic review highlights an area of potential expansion for the field of AI in medical image interpretation.There is limited knowledge of A systematic review of artificial intelligence tools for chronic pulmonary embolism in CT. This systematic review provides an assessment on research that examined deep learning algorithms in detecting CTEPH on CTPA images, the number of studies assessing the utility of deep learning on CTPA in CTEPH was unclear and should be highlighted